Ambient vibration testing and seismic analysis of a masonry chimney - Valter Lopes (2009)
At the end of the XIX and the beginning of the XX century there was a considerable development in Portugal, characterized by the flourishing of many industrial plants. Brick masonry chimneys represent some of the most interesting elements of the industrial architectural heritage of that time. The paper shows the study and analysis of a chimney from a former ceramic factory located near Porto, Portugal, and that now is part of a cultural and leisure public park. The focus in this work is given on the detailed in-situ survey of the chimney, involving: geometrical characterization, visual inspection, with damage registration, and structural and material assessment based on in situ dynamic tests. This survey allowed assessing the in-situ mechanical characteristics of the chimney and to construct a realistic numerical model to evaluate the seismic vulnerability of the chimney. Two different approaches regarding the chimney damage state were followed for the calibration of the numerical model. The models from both approaches were afterwards subjected to accelerograms matching the chimney site conditions and the responses were analysed and compared. The importance of a good mechanical characterization of the materials involved is underlined in this analysis.